Analytics na educação: Da gestão personalizada da atividade de ensino a definição de políticas institucionais - Ferreira, Sérgio André (2016)
Pressured by the context of the Information Society, the Higher Education Institutions (HEIs) are introducing innovation by means of technology, investing in technological platforms - especially the LCMS -, for the development of their educational purpose. These platforms are complemented by other technological systems to support the management of the different aspects of the HEIs’ life. The activity of students, teachers and administrators in these systems result in a huge trail of clicks, which is reflected in the huge volume of data registered. The Analytics idea is simple and has a very high transformative potential: the use of this data allows for a more informed decision-making process, opening the door to a new model in the management of HEIs in educational fields and organizational efficiency. In this study, in theory, the theme of Analytics in the Information Society and within the HEIs is contextualized. In the practical field, it presents two main contributions i) the demonstration of the use of Analytics in practice, from the customized management of the teaching activity to the definition of institutional policies; ii) development of two Analytics systems (Learning Analytics and Academic Analytics) for the management of the educational activity from the data made available by technological subsystems in use at the Universidade Católica Portuguesa - Porto.